Miglustat Reverts the Impairment of Synaptic Plasticity in a Mouse Model of NPC Disease - G. D’Arcangelo; D. Grossi; M. Racaniello; A. Cardinale; A. Zaratti; S. Rufini; A. Cutarelli; V. Tancredi; D. Merlo; C. Frank (Neural Plasticity)
Niemann-Pick type C disease is an autosomal recessive storage disorder, characterized by abnormal sequestration of unesterified cholesterol within the late endolysosomal compartment of cells and accumulation of gangliosides and other sphingolipids. Progressive neurological deterioration and insurgence of symptoms like ataxia, seizure, and cognitive decline until severe dementia are pathognomonic features of the disease. Here, we studied synaptic plasticity phenomena and evaluated ERKs activation in the hippocampus of BALB/c NPC1−/− mice, a well described animal model of the disease. Our results demonstrated an impairment of both induction and maintenance of long term synaptic potentiation in NPC1−/− mouse slices, associated with the lack of ERKs phosphorylation. We then investigated the effects of Miglustat, a recent approved drug for the treatment of NPCD. We found that in vivo Miglustat administration in NPC1−/− mice was able to rescue synaptic plasticity deficits, to restore ERKs activation and to counteract hyperexcitability. Overall, these data indicate that Miglustat may be effective for treating the neurological deficits associated with NPCD, such as seizures and dementia.